Toward a more dialogic pedagogy: changing teachers' beliefs and practices through professional development in language arts classrooms. (2nd January 2017) - Wilkinson, Ian A. G.; Reznitskaya, Alina; Bourdage, Kristin; Oyler, Joseph; Glina, Monica; Drewry, Robert; Kim, Min-Young; Nelson, Kathryn
ABSTRACT: In this paper, we report findings from the second year of a three-year research and professional development program designed to help elementary school teachers engage in dialogic teaching to support the development of students' argument literacy. We define argument literacy as the ability to comprehend and formulate arguments through speaking, listening, reading, and writing. The professional development program was focused on promoting teachers' use of a specific type of talk called 'inquiry dialogue' to achieve the goal of developing students' argument literacy. We used a single-group pretest-posttest design to assess the impact of the professional development on teachers' epistemological beliefs and their enactment of inquiry dialogue in text-based discussions. Our analyses of videotaped discussions at the beginning and end of the year showed that there were substantial improvements in teachers' facilitation of inquiry dialogue and in the quality of students' argumentation during discussions. Contrary to expectations, however, there were no changes in teachers' epistemology; teachers' beliefs about knowledge and knowledge justification remained at a relativist stage throughout the course of the program, suggesting that teachers continued to view all opinions as equally valid and regard arguments and the use of reasons and evidence as idiosyncratic.